PENGARUH DIGITAL MARKETING, WORD OF MOUTH (WOM), DAN CITRA SEKOLAH TERHADAP KEPUTUSAN ORANG TUA MEMILIH SD AG BEKASI - Brigita Maharani Parama Putri; Yunus Handoko; Ike Kusdyah Rachmawati (Smart Education, 2026)
The increasingly competitive competition among elementary schools has encouraged schools to develop effective marketing strategies. The development of digital marketing, word of mouth, and school image has become important factors considered by parents when selecting a school for their children. The fluctuation in the number of new students at AG Elementary School, Bekasi indicates the need to examine the influence of the analyze the influence of digital marketing, word of mouth, and school image on parent’s school selection decisions. This study aims to analyze the influence of digital marketing, word of mouth, and school image on parent’s decisions to choose AG Elementary School, Bekasi. This research employed a quantitative approach using survey method involving 64 parents of newly enrolled students selected through a saturated sampling technique. Data were collected using questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results indicated that digital marketing has no significant effect on parent’s school selection decisions, while word of mouth and brand image have a positive and significant effect on parent’s school selection decisions. Simulataneously, the three independent variables have significant effect on parent’s decisions to choose AG Elementary School.